RRx-001 Radioprotection: Enhancement of Survival and Hematopoietic Recovery in Gamma-Irradiated Mice - Jurgensen, Kimberly J.; Skinner, William K. J.; Oronsky, Bryan; Abrouk, Nacer D.; Graff, Andrew E.; Landes, Reid D.; Culp, William E.; Summers, Thomas A.; Cary, Lynnette H. (Frontiers in Pharmacology, 2021)
The present studies evaluate the in vivo prophylactic radioprotective effects of 1-bromoacetyl-3, 3-dinitroazetidine (RRx-001), a Phase III anticancer agent, after total body irradiation (TBI), in lethally and sublethally irradiated CD2F1 male mice. A single dose of RRx-001 was administered by intraperitoneal (IP) injection 24 hours prior to irradiation with 9.35 Gy, the dose lethal to 70% of untreated mice at 30 days (LD70/30), only 33% of mice receiving RRx-001 (10 mg/kg) 24 hours prior to total body irradiation (TBI) died by day 30, compared to 67% in vehicle-treated mice. The same pretreatment dose of RRx-001 resulted in a significant dose reduction factor of 1.07. In sublethally TBI mice, bone marrow cellularity was increased at day 14 in the RRx-001-treated mice compared to irradiated vehicle-treated animals. In addition, significantly higher numbers of lymphocytes, platelets, percent hematocrit and percent reticulocytes were observed on days 7 and/or 14 in RRx-001-treated mice. These experiments provide proof of principle that systemic administration of RRx-001 prior to TBI significantly improves overall survival and bone marrow regeneration.